Production of recombinant goose parvovirus origin VP2 protein based on baculovirus expression system - Ozbek, Remziye; Atasoy, Mustafa Ozan; Turan, Turhan; Isidan, Hakan; Abayli, Hasan; Sahna, Kezban (Urmia Univ, 2026)
Goose parvovirus causes major economic losses in the waterfowl industry due to the high mortality. Therefore, it is essential to establish protection/control objectives in the fight against the disease. The genome of goose parvovirus consists of three structural proteins, including VP1, VP2, and VP3. The VP2 is a candidate antigen in developing vaccines and diagnostic kits. This study aimed to produce the VP2 protein from a local goose parvovirus strain that causes serious infections in geese in Turkiye using the baculovirus expression vector system. To achieve this, the VP2 gene was first amplified by polymerase chain reaction, followed by purification and insertion into the pENTR (TM)/TEV/D-TOPO (TM) entry vector. Then, the target gene in the pENTR (TM)/TEV/D-TOPO (TM) vector was transferred to linear N-Term BaculoDirect (TM) DNA through LR recombination (site-specific recombination between attL and attR sites). The construct was transfected into Spodoptera frugiperda cells. To verify the production of baculoviral virions, a band of approximately 600 bp in length was obtained as a result of polymerase chain reaction amplification using external primer sets for both the VP2 gene and expression vector. The obtained band was purified and sequenced for confirmation. In addition, to confirm the production of the recombinant protein, western blot analysis was conducted utilizing the V5 epitope located at the N-terminus of the expressed protein, resulting in the detection of a similar to 65.00 kDa band corresponding to the VP2 gene. To detect protein expression in S. frugiperda cells infected with the recombinant baculovirus, immunofluorescence analysis was performed using the same epitope. (c) 2026 Urmia University. All rights reserved.
Keywords: Baculovirus; Expression; Goose parvovirus; Recombinant protein; VP2